Regioselective Synthesis of Dihydropyridocoumarin and Phenanthrolinone Derivatives via Iron(III) Chloride Mediated Intramolecular Cyclization - Majumdar, K. C.; Ponra, Sudipta (Synthesis, 2014)
Potentially bioactive angular dihydropyridocoumarin and phenanthrolinone derivatives are synthesized in good to excellent yields using readily available iron(III) chloride (FeCl3) as the catalyst. The process is very simple, straightforward and inexpensive, and provides a diverse range of pyranoquinolone or phenanthrolinone derivatives, via a 6-endo-dig mode of cyclization, starting from simple and easily available 6-(N-propargyl)aminocoumarin and -quinolone derivatives.
Keywords: pyranoquinolone; phenanthrolinone; iron(III) chloride; Sonogashira coupling; 6-endo-dig cyclization